"Appled audio-visual resources fo the teaching of english as a second language for twelfth grade students at Colegio Secundario Las Lajas 2009" - Castro Polanco, Laure Lynn; Lezcano Girón, Marilin Iveth (David, Panamá : UDELAS, 2010)
It is important to state here that the purpose of this investigation is to applied didactic methodology supported by audio visual techniques and that are applicable to the content of the twelfth grade english as a second language program, for which study Colegio Secundario Las Lajas was chosen as the target institutions subject of this research.
CONTENT Chapter I Reason for this research Chapter II Theoretical framework 2.1. Description of the educational center 2.2. The english language 2.2.1. English language importance 2.2.2. The future of the english language 2.3. The teaching process 2.3.1. Teaching concept 2.3.2.Purpose and aims of learning process 2.3.3. The english of the english language 2.3.4. Methods and audio-visual materials in teaching english as second language 2.4. The learning process 2.4.1. Concept 2.4.1.1. The learning process 2.4.2. Types of learning 2.4.2.1. Verbal learning 2.4.2.2. Learning concepts 2.4.2.3. Principles learning 2.4.2.4. Resolution of problem 2.4.2.5. Learning determinated to a sign 2.4.3. Perception 2.4.4. Motivation 2.4.1.1. Types of students acording to motivation 2.5. Audio-visual teaching resources 2.5.1. History and means and audio-visual materials 2.5.2. Concept 2.5.3. Teaching systematic planning using audio-visual materials 2.5.4. Puporse of audio-visual means 2.5.4.1. To bring the students near to the reality of what wants to be taught 2.5.4.2. To motivate the class 2.5.4.3. To facilitate perception and comprehensions or facts and concept 2.5.4.4. To concentrate and to illustrate what is exhibiting verbally 2.5.4.5. To save effort to lead the students the comprehensionof facts and concepts And other more Chapter III Methodological framework Chapter IV Investigation results Chapter V Proposition: Didactic strategies applied to the use of audio visual resources it the teaching and learning process of english as a second language in the twelfth level program Chapter VI CONCLUSIONS RECOMMENDATIONS BIBLIOGRAPHY CHAPTER VII ATTACHMENTS
Incluye Content
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- TEACHING; ENGLISH -- TESIS DE LICENCIATURA -- DIDACTIC; FACULTAD DE EDUCACIÓN SOCIAL; DEPARTAMENTO DE INGLÉS; LICENCIATURA EN DOCENCIA EN INGLÉS; COLEGIO SECUNDARIO LAS LAJAS - CHIRIQUÍ